2021
DOI: 10.12998/wjcc.v9.i14.3252
|View full text |Cite
|
Sign up to set email alerts
|

Burden of atrial fibrillation in patients with rheumatic diseases

Abstract: BACKGROUND Studies have suggested that atrial fibrillation (AF) in patients with rheumatic diseases (RD) may be due to inflammation. AIM To determine the highest association of AF among hospitalized RD patients and to determine morbidity and mortality associated with AF in hospitalized patients with RD. METHODS The National inpatient sample database from October 2015 to December 2017 was analyzed to identify hospitalized patients with RD with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…Each admission contains information on patient characteristics including demographics, comorbidities, complications, and primary and secondary discharge diagnoses. This has been explained in detail in previous studies [ 3 , 4 ]. The International Classification of Disease, 9th revision, Clinical Modification (ICD 9-CM) codes were used to identify diagnosis in the NIS database [ 5 , 6 ].…”
Section: Methodsmentioning
confidence: 77%
“…Each admission contains information on patient characteristics including demographics, comorbidities, complications, and primary and secondary discharge diagnoses. This has been explained in detail in previous studies [ 3 , 4 ]. The International Classification of Disease, 9th revision, Clinical Modification (ICD 9-CM) codes were used to identify diagnosis in the NIS database [ 5 , 6 ].…”
Section: Methodsmentioning
confidence: 77%
“…Both AF and gout have similar risk factors. According to the literature, the prevalence of AF in patients with gout is Frontiers in Pharmacology frontiersin.org higher than in those without, although the mechanisms of both conditions remain unclear (Kim et al, 2016;Singh and Cleveland, 2018;Khan et al, 2021). Although the pathogenesis of AF remains only partially understood, the current evidence links AF to inflammation and autonomic nervous system complications.…”
Section: Mechanism Of Atrial Fibrillation Development In Patients Wit...mentioning
confidence: 99%
“…The prevalence of gout in Taiwan is higher than in other countries such as the United Kingdom (2.49%) and the United States (3.9%) ( Kuo et al, 2015 ). Gout results from uric acid deposition; the uric acid links not only to acute or chronic arthritis but also cardiovascular disease ( Kim et al, 2016 ; Singh and Cleveland, 2018 ; Dehlin et al, 2020 ; Khan et al, 2021 ). Past studies demonstrated that the prevalence of atrial fibrillation (AF) and cardiovascular mortality is higher in patients with gout than in those without ( Kim et al, 2016 ; Singh and Cleveland, 2018 ; Khan et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We relied on diagnosis codes for cancer subtypes and AF, which could potentially lead to exposure and outcome misclassification, however, both ICD codes for AF and cancers are validated and used in several studies. 23 , 24 We did not investigate the severity and stages of cancers which could affect the development of AF. In addition, we did not study the effect of chemotherapy on the development of AF.…”
Section: Limitationmentioning
confidence: 99%